METAFORA PADA DESAIN KAOS PRODUKSI KAPUYUAK DAN KONCO CLOTHING - Chesil Rulianty; Lindawati Lindawati; Bahren Bahren; Herry Nur Hidayat (Jurnal Elektronik WACANA ETNIK, 2017)
This article describes the use of metaphoric words of T-shirt design produced by the Kapuyuak and Konco Clothing stores. T-shirts in both stores contain many metaphors about the daily life of Minangkabau people. This study discusses metaphorical forms and functions in the product's design of those two shops. The theory used is the theory of the metaphor form proposed by Stephen Ullman and the theory of functions by Geoffrey Leech.The results show metaphorical forms in the T-shirts design produced by the Kapuyuak and Konco Clothing stores, which are 6 anthropomorphic metaphors, 4 animal metaphors, 7 metaphors from concrete to abstract, and 3 synaesthetic metaphors. Whereas, the functions found are 4 informational functions, 4 expressive functions, 1 directive function, 1 fatigue function, and 10 aesthetic functions.Keywords: metaphor, shirt design, metaphorical form, metaphorical function